Gadamer and the hermeneutical problem of psychoanalytic interpretation - Gracia Gómez, Alfonso (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
There is a privileged position to analyze the possible relationship between philosophy and psychoanalysis, and this is through hermeneutics. Not only Ricoeur, many authors, on either side of the dispute, have expressed their views about the similarities and the differences between psychoanalysis and philosophical hermeneutics, which wants to serve as a vehicle to understand the interpreting essence of human beings. Because of this, authors such as Heidegger and Gadamer have been called to express their positions on the knowledge of the unconscious, to evaluate the way of putting in contact the essence of psychoanalysis as talking cure and the internal reference of philosophy as dialogue. To this end, Gadamer deeply mistrusts Ricoeur's conception of psychoanalysis as “hermeneutics”, and for this focuses its criticisms on two core aspects of psychoanalytic interpretation: the fact that it is conducted through techniques, on the one hand, and the concomitant effect that in the psychoanalytic cure there isn't any “authentic”, but rather frustrated dialogue.
Keywords: Hermeneutics; Psychoanalysis; Understanding; Interpretation; Tecnique